THEATRE THERAPY-METHODS OF PSYCHOTHERAPY A PART OF A COMPLEX PROGRAM FOR RESOCIALIZATION AND DELIMITATION OF THE PLACE BETWEEN MENTAL HEALTH SERVICES (University Arena, 2025)
Theatre therapy involves passing through a complex program of specific activities which involves the stimulation of expressing of the feelings, an aspect that leads to the recognition of the human potential in each person and  the development of a culture of dignity and respect. Theatre developes social abilities, abilities that contribute to personal development, thus, ”the actor managing to progress in his discover of himself and to become more human, more empathetic closer to social reality.
Keywords: theatre; social abilities; mintal health